Do health provider–patient relationships matter? Exploring dentist-patient relationships and oral health-related quality of life in older people. (25th November 2013) - Muirhead, Vanessa Elaine; Marcenes, Wagner; Wright, Desmond
Abstract: Background: patient experience is now a key parameter in health care. Yet, very little is known about the possible impact of dentist–patient relationships on patient-centred outcomes including older peoples' oral health-related quality of life (OHRQoL). Objective: this study assessed the relationship between OHRQoL and dentist–patient relationships related to perceived unmet dental needs; shared decision-making; time spent discussing oral health problems; respect and confidence and trust. Participants: older people aged 65 years and over living in East London, UK in 2011. Methods: a cross-sectional study using stratified random sampling recruited a representative sample of older people ( n = 772). Participants completed an oral examination and a structured questionnaire including the Oral Health Impact Profile-14 (OHIP-14) measuring OHRQoL and five dentist–patient relationship questions taken from the UK 2009 Adult Dental Health Survey. Multivariate Poisson regressions modelled the association between OHRQoL and dentist–patient factors adjusting for socio-demographic factors, clinical oral indicators, and dental attendance. Results: having a perceived unmet need for dental treatment (PRR = 1.84; 95% CI: 1.32, 2.56) and expressing a lack of trust and confidence in one's dentist (PRR = 1.74; 95% CI: 1.01, 2.98) were significant predictors of poor OHRQoL among older people. Conclusions: these findings suggest that older people with unmet dental needs and those who expressed a lack of trust and confidence in their dentist were more likely to experience poor OHRQoL reinforcing the importance of the dental patient experience in healthy ageing and well-being.